Neurophysiology of learning in basic skills of laparoscopic surgery in undergraduate students - Granados-Romero, Juan José; Valderrama-Treviño, Alan Isaac; Barrera-Mera, Baltazar; Espejel-Deloiza, Mariana; Contreras-Flores, Ericka Hazzel; Mendoza-Barrera, Germán Eduardo; Méndez-Celis, Carlos Aarón; Romo-García, José Javier (International Journal of Research in Medical Sciences, 2016)
Background: The development and progress in laparoscopic surgery requires greater emphasis on surgical skills, developing skills in undergraduate students allows them to be at the forefront in health demands. Methods: An experimental and descriptive study of a group of 30 undergraduate students of the Faculty of Medicine. They attended 30 hours of theoretical and practical sessions distributed by 10 sessions, supported by basic simulators minimally invasive, being evaluated by checklist. Their brain activity was monitored with an electroencephalography before and after the development of skills. Results: It was observed that the average necessary for the acquisition of skills is 5 sessions. The competition in which further progress was observed is video assistance. There is an increase in the activity of the prefrontal cortex on the electroencephalography. Conclusions: A series of neurophysiologic processes involved in learning of laparoscopic surgery are described. Laparoscopic skills development lies in keeping them updated on the teaching-learning, where the use of simulators is growing.